Internalizing Pancasila Values among the Younger Generation in Jakarta in the Context of the 2024 Presidential Election in Indonesia - Ririt Yuniar; Titania Fattiha Ahsan (Ikatan Sarjana Komunikasi Indonesia, 2024)
The internalization of Pancasila values among the younger generation is significant for a more in-depth study ahead of the 2024 presidential election in Indonesia. This has become a hot issue as material for study, especially after the 2024 presidential and vice presidential candidate debate took place. This research aims at 3 things: First, to inform the importance of internalizing the Pancasila values among the younger generation to welcome the 2024 election; Second, to instill Pancasila values in the younger generation in responding to currently developing political dynamics; Third, to strengthen implementation of Pancasila values in political ethics by socializing them among the younger generation to realize peaceful elections in 2024.Â The mixed method used for this research is quantitative data collection, using qualitative descriptive techniques with text analysis. The distribution of questionnaires conducted directly and online is based on the theory of social reality construction, with the concept of internalization being the focus. This research shows 3 things: First, the younger generation received information regarding the importance of internalizing Pancasila values in creating peaceful elections in 2024. Second, researchers succeeded in socializing the effort to instil Pancasila values in the younger generation in responding to political dynamics in the 2024 elections. Third, ethical politics in peaceful elections have been socialized by strengthening Pancasila values to make the situation more conducive to implementing peaceful elections. It is hoped that this research can become a consistent and sustainable national movement for the upcoming elections and prepare the younger generation to have a peaceful and constructive mentality.